Technology of recycling radioactively contaminated metal by the method of melting - Balakin, Valeriy; Mashinistov, Viktor; Galkin, Oleg; Bilan, Kostiantyn (Eastern-European Journal of Enterprise Technologies, 2016)
A technology is proposed of recycling radioactively contaminated metal by the method of melting, based on the effect of self deactivation. In accordance with this technology, radioactively contaminated metal is loaded into a melting furnace without the operation of preliminary decontamination. In the process of melting, the radionuclides located on its surface pass into molten metal and are distributed evenly in its volume. Beyond the limits of products made of this metal is the gamma-radiation of a small part of the radionuclides contained by them. Gamma radiation of the remaining radionuclides, as well as alpha-radiation and beta-radiation of radionuclides, is completely absorbed in the volume of metal. As a result, the process of melting led to a considerable decrease in the power of ionizing radiation on the surface of metal. That is why this effect can be named the self deactivation of metal during its melting. At the same time, some radionuclides evaporate while a part of them passes to slag, further purifying metal. As a result, the conditions are created for obtaining the metal that is safe as far as the radiation is concerned. The ratios are presented, which make it possible to calculate the amount of gamma-emitting radionuclides that can be loaded to a melting furnace in order to ensure a required level of the power of gamma radiation on the surface of the smelted metal. It was demonstrated that the criterion of evaluation of radiation safety of metal is the power of gamma radiation on its surface. In the implementation of this approach, both the known technologies of melting metals and the equipment of melting furnaces are not in fact complicated. This makes it possible to considerably increase technical and economic indicators of the process of recycling radioactively contaminated metal and to decrease substantially the volumes of accumulated radioactive wastes.